UMPSA conducts campaign for Disposal of Quranic Manuscripts and Printed Quranic Text Materials - Jamilah Bebe, Mohamad (UMPSA, 2024)
PEKAN, 25 November 2024 – The Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), successfully conducted the Campaign for the Disposal of Quranic Manuscripts and Printed Quranic Text Materials, held in conjunction with the Public Sector Conducive Ecosystem Week (EKSA) recently.